Creativity, Conviviality, and Civil Society in Neoliberalizing Public Space: Changing Politics and Discourses in Skateboarder Activism From New York City to Los Angeles. (December 2019) - Chiu, Chihsin; Giamarino, Christopher
Neoliberal urbanism often draws critiques because it privatizes public space and excludes specific social groups whose interests are not in line with the development goals of local states and corporations. This article, through an exploration of the politics and discourses of urban skateboarding, suggests that this clear distinction, between entrepreneurialism and community–based place making, may fail to explain transformative changes occurring in public space today. Comparing two grassroots activist campaigns at the Brooklyn Banks in New York City (NYC) and West LA Courthouse in the city of Los Angeles (LA), this article explains the ways in which skateboarders leverage specific neoliberal ideologies to claim their right to these two settings. In both cases, skateboarders save spaces through entrepreneurial urban means that bolster neoliberal values while retaining the tactical nature of their activities. Although both activist movements pursue the common values of authenticity, entrepreneurship, and private funding, they employ different discourses to reclaim public space. The NYC skaters frame a security discourse, which ultimately limits their continual access to the Brooklyn Banks. The LA skate community, on the contrary, constructs a spontaneity discourse, characterized by creativity, conviviality, and civil society, successfully transforming the West LA Courthouse into a legalized skate plaza. Our findings suggest that skateboarding communities and their spatial activism are resilient enough to articulate different rationales and successfully fight to transform public spaces into urban commons. However, we argue that 'the discourses' matter significantly in the processes and outcomes of activist mobilizations occurring within neoliberalizing public space.